Analisis Komposisi dan Struktur Komunitas Hasil Tangkapan Trawl Ikan Di Perairan Muara Sabak Timur Kabupaten Tanjung Jabung Timur - Rais, Amin; Yurleni, Yurleni; Febrina Rolin; Nurhayati, Nurhayati; Fauzan Ramadan; Magwa, Rizky Janatul (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2025)
East Tanjung Jabung Regency is part of Jambi Province and is directly adjacent to the sea. This study aims to determine the composition and structure of the trawl catch community. The research was conducted in Lambur Luar Village, East Muara Sabak District, East Tanjung Jabung Regency, Jambi Province, on March 19-May 25, 2025. The method used in this study is a survey method with purposive sampling technique. The data obtained were analyzed on the composition of the catch, the proportion of the catch, the diversity, evenness, and dominance of the catch. The results of the study showed that there were 53 types of fish caught, the diversity index value was 1.915 (medium), the evenness index value was 0.480 (medium), and the dominance index value was 0.219 (low). From the results of the study, it can be concluded that 53 catches were obtained consisting of 3 main catches, 42 types of by catch, and 8 types of discards. The proportion of catches showed HTU of 3.07%, HTS of 57.14%, and HTB of 39.79%. The value of the diversity index is in the medium category, as well as the value of evenness which is also included in the medium category, while the dominance value is relatively low.